Penerapan Bimbingan Kelompok untuk Meningkatkan Motivasi Belajar Peserta Didik SMP Negeri 24 Surabaya - Muhammad, Muhammad; Rahmawati, Irma; Nikmah, Lailatul; Rizquna4, Melina Elfani; Nuraini, Sabrina Icha; Cahyani, Ninda Ayu Putri; Moesarofah, Moesarofah (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
This study aims to determine the effectiveness of group guidance in improving student learning motivation at SMP Negeri 24 Surabaya. The background of this study is based on the low learning motivation of some eighth-grade students identified through initial questionnaires and teacher observations. This low motivation has an impact on a lack of enthusiasm for learning, decreased concentration, and suboptimal learning outcomes. Therefore, an intervention is needed in the form of group guidance services that are believed to facilitate students to share experiences, obtain social support, and foster a positive attitude towards learning activities. This study uses a Classroom Action Research (CAR) approach implemented in two cycles. The research subjects were eighth-grade students who have low levels of learning motivation. Data collection was carried out through learning motivation questionnaires, interviews, and observations. Data were analyzed descriptively quantitatively and qualitatively by comparing motivation scores before and after treatment and observing changes in student attitudes in learning activities. The results showed a significant increase in learning motivation questionnaire scores after participating in group guidance, accompanied by changes in behavior that are more active and enthusiastic in participating in learning. The contribution of this research confirms that group guidance is an effective and applicable service to help increase students' learning motivation in secondary schools.